Stochastic Failure Mode Effect And Critical Analysis (SFMCEA) on Repair and Retrofitting Projects - Albasyouni, Wahbi (LPPM Universitas Andalas, 2022)
FMEA is a known method in risk management that de-fines the failure that might happen and identifies its hazards on the system; this procedure can be done using the risk priority number “RPN” analysis system. This method is applied on a real repair project “Sheraton Hotel” located in Cairo city near the Nile River where they had to make urgent repairs to avoid failure and collapse of the building. This study concentrated on developing the results and most common failures that might happen in any emergency project by determining the severity, occurrences, and detection to get the overall RPN of each failure. Two methods were used to rank the risks, the first one is the traditional approach which is based on getting one value for the severity, occurrence, and detection. On the other hand, the other method is getting a range of values (3 values) for the severity occurrence, and detection. The results showed that using the traditional form of RPN resulted in three major risks such as ineffective work penalties, complex contractor’s policies, and risks related to contract agreement. On the other hand, the use of a probabilistic analysis showed that the top risks are ineffective work penalties, problems with contract agreement, and unfavorable contract.